1998
DOI: 10.1103/physrevb.57.9690
|View full text |Cite
|
Sign up to set email alerts
|

Isotope shift in semiconductors with transition-metal impurities: Experiment and theory applied toZnO:Cu

Abstract: Isotope shifts for various lines associated with excitations of transition-metal impurities in semiconductors are considered. Special attention is paid to ZnO:Cu, for which experimental results are presented. Isotope shifts are measured for the so-called photoluminescence ␣ and ␤ zero-phonon lines associated with excitations of bound excitons, and of the zero-phonon line associated with the intracenter Cu 2ϩ (2 T 2 Ϫ 2 E) transition. These shifts appear to be negative and nearly equal. A theoretical model expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 19 publications
2
16
2
Order By: Relevance
“…A possible physical mechanism of the AMs is that the impurity centers break the translational symmetry of the crystal, thereby relaxing the conservation of wave vector; they can lead to scattering by phonons in the host materials that have wave vectors far from the zone center [27]. Comparing the Raman spectra of Cudoped ZnO film with the reports by Dahan et al and Broser et al [28,29], one can find that the AMs can even be observed under non-resonant excitation (E < E a = 2.85986 eV). The difference may be due to that the Cu dopant concentration in our experimental condition is much more than that of their reports (250 ppm), but precision physical reason certainly deserves further study.…”
Section: Resultsmentioning
confidence: 97%
“…A possible physical mechanism of the AMs is that the impurity centers break the translational symmetry of the crystal, thereby relaxing the conservation of wave vector; they can lead to scattering by phonons in the host materials that have wave vectors far from the zone center [27]. Comparing the Raman spectra of Cudoped ZnO film with the reports by Dahan et al and Broser et al [28,29], one can find that the AMs can even be observed under non-resonant excitation (E < E a = 2.85986 eV). The difference may be due to that the Cu dopant concentration in our experimental condition is much more than that of their reports (250 ppm), but precision physical reason certainly deserves further study.…”
Section: Resultsmentioning
confidence: 97%
“…From the scientific viewpoint, studies of the SGB have involved a wide variety of topics, such as the theory of intermediately bound excitons and the nature of the isotope shift in the ground and excited states. [10][11][12][13] Proof of the involvement of Cu in the SGB emission would provide a clear experimental underpinning of the assumptions behind such studies.…”
Section: -4 9 A)mentioning
confidence: 99%
“…The green luminescence band observed around 2.58 eV in undoped ZnO has been the subject of investigation by many workers [27][28][29][30]. This band has been attributed to Cu impurities in ZnO single crystal [10].…”
Section: Resultsmentioning
confidence: 97%